The Relationship between Trade and Foreign Direct Investment in South Asian Countries: A Panel Data Approach - RejaulKarim, Md; Islam, Rakibul; Hassan, Md. Mahmudul (Economic Journal of Nepal, 2013)
The major objective of this paper is to examine the relationship among FDI, export and import in south Asian countries (Bangladesh, India and Pakistan) using panel data for the period from 1986 to 2013. The integration order has been identified using Levin, Lin & Chu, I m, Pesaran and Shin W-stat, ADF Fisher Chi-square and PP- Fisher Chi- square unit root test. The Kao test has been applied to investigate the long run relationship among variables. Finally a panel Vector Error Correction Model has been built to present the dynamic adjustment in relation of FDI, export and import. The tests results show that all variables are co integrated indicating a stable long run relationship among them. But overall short run relation is significant for FDI and import equation whereas for export equation is unable to generate any short run relationship. And none of the equation yields any short run causal relationship. The policy implication of this analysis is that FDI, export and import are closely related term; change in any single one depends on change in these two variables in short run except export while persisting long run relationship.